Regional air pollution severity affects the incidence of acute myocardial infarction triggered by short-term pollutant exposure: a time-stratified case-crossover analysis - Yen, Chih-Chien; Chen, Ping-Ling (Environmental science and pollution research international, 2022)
Long-term exposure to air pollution results in a high incidence of cardiovascular disease. Many studies have found that short-term exposure to air pollution can trigger acute myocardial infarction. This study aims to determine whether results in areas with different levels of severity of air pollution are similar. The study design is a time-stratified case-crossover analysis. This was a retrospective study based on hospital medical records. The study period was since 1 January 2017 to 31 December 2018. Research data were collected from Taoyuan Hospital, located in an area with low severity of pollution, and Taichung Hospital, located in an area with high severity of pollution. The correlation between short-term air pollution exposure and acute myocardial infarction was analyzed. The correlation between short-term exposure to ambient air pollutants and acute myocardial infarction was not significant for the cases collected from Taoyuan Hospital (PM 2.5 OR: 1.006 and 95% CI: 0.995–1.017; PM 10 OR: 0.996 and 95% CI: 0.988–1.003). However, for the cases collected from Taichung Hospital, short-term exposure to ambient PM 2.5 (odds ratio: 1.021; 95% confidence interval: 1.002–1.040) and PM 10 (odds ratio: 1.010; 95% confidence interval: 1.001–1.020) resulted in high incidence of acute myocardial infarction. Short-term pollutant exposure will increase the incidence of acute myocardial infarction based on the severity of regional air pollution. In addition to addressing traditional cardiovascular disease risk factors, the government must formulate relevant policies for reducing air pollution and the resulting hazards to citizens’ health.